2012
DOI: 10.1590/s0100-55022012000500002
|View full text |Cite
|
Sign up to set email alerts
|

Percepções de alunos de medicina sobre marketing médico

Abstract: INTRODUÇÃO: Marketing médico é um assunto controverso, principalmente no que concerne a princípios éticos. Portanto, frente à competição acirrada de mercado, é necessário o preparo profissional. Conhecer a percepção dos alunos de Medicina pode auxiliar na estruturação de alternativas de capacitação. METODOLOGIA: Inicialmente, identificaram-se crenças sobre marketing médico através de grupo focal composto por 12 alunos. Com base nesses dados, dez afirmações para avaliar atitudes foram aplicadas aos alunos de um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 8 publications
0
7
1
9
Order By: Relevance
“…Medical and dental marketing is part of a relatively recent reality that requires the adjustment of the professional's ethical behaviour 13 . This new reality can be easily seen after verifying the literature, which showed that in 2005 the two most popular media used in dentistry were direct mail and telephone directory 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical and dental marketing is part of a relatively recent reality that requires the adjustment of the professional's ethical behaviour 13 . This new reality can be easily seen after verifying the literature, which showed that in 2005 the two most popular media used in dentistry were direct mail and telephone directory 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This new reality can be easily seen after verifying the literature, which showed that in 2005 the two most popular media used in dentistry were direct mail and telephone directory 14 . Also, just over five years ago, marketing was still an issue unknown to most medical students 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Também há evidências incipientes de que um processo de tutoria nesse contexto ampliado pode ser realizado e mensurado. 8 A relação entre tutor e tutorado(s) tem características especiais. Apesar de ser uma relação assimétrica, pois o tutor deve ter formação específica e é selecionado por ser reconhecido como um modelo a ser seguido, ela não é uma relação passiva.…”
Section: Caracterizando a Educação Tutorialunclassified
“…O trabalho, além de trazer um conhecimento abrangente para o grupo sobre um tema percebido como pouco claro para os estudantes de medicina, propiciou maiores estudos sobre o método científico e foi publicado na Revista Brasileira de Educação Médica em 2012. 15…”
Section: Marketing Médicounclassified